2016
DOI: 10.1111/pin.12408
|View full text |Cite
|
Sign up to set email alerts
|

NAB2‐STAT6 gene fusion and STAT6 immunoexpression in extrathoracic solitary fibrous tumors: the association between fusion variants and locations

Abstract: Solitary fibrous tumor (SFT) is a rare mesenchymal neoplasm harboring NAB2-STAT6 fusion, which drives STAT6 nuclear relocation. For extrathoracic SFTs, the clinical relevance of this molecular hallmark remains obscure. We assessed STAT6 immunoexpression for 61 extrathoracic SFTs exclusive of the meninges and head and neck, and 25 had analyzable RNAs to distinguish fusion variants by RT-PCR. The immunohistochemical and molecular findings were correlated with clincopathological features and disease-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
2
32
1
2
Order By: Relevance
“…Relationships were also examined between NAB2-STAT6 gene fusion variants, body site location, age and tumour size, and clinical outcomes of solitary fibrous tumours. Although the study did not demonstrate significant relationships, it highlights the potential use of fusion variants for outcome prediction 22. STAT6 immunohistochemistry probably suffices for diagnostic evaluation of solitary fibrous tumours.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Relationships were also examined between NAB2-STAT6 gene fusion variants, body site location, age and tumour size, and clinical outcomes of solitary fibrous tumours. Although the study did not demonstrate significant relationships, it highlights the potential use of fusion variants for outcome prediction 22. STAT6 immunohistochemistry probably suffices for diagnostic evaluation of solitary fibrous tumours.…”
Section: Discussioncontrasting
confidence: 56%
“…An understanding of solitary fibrous tumours at this extrapleural site has become increasingly relevant with the discovery of the molecular hallmark NAB2-STAT6 gene fusion. Such genetic aberrations may improve diagnostic and prognostic accuracy and may foster elucidation of additional molecular mechanisms involved in tumorigenesis 2 13 16 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the difference in terminology of SFT/HPC between meninges and other sites, it is difficult to compare the histology in all primary sites. While there were some reports that there was no statistical correlation between the histological variants and the NAB2-STAT6 fusion gene variants [25,26,28,31], Barthelmeb reported that there was a significant correlation between NAB2-STAT6 fusion gene and histological feature; fibrous SFT, cellular SFT and HPC in intrathoracic region, head and neck, and soft tissue and that most tumors with NAB2 exon 4-STAT6 exon 2/3 fusion are classical fibrous pleuropulmonary SFTs with a benign appearance, and most tumors with NAB2 exon 6-STAT6 exon 16/17 are cellular SFT and HPCs in the retroperitoneum and pelvis with cellular appearance, increased mitotic activity [12]. Based on Fritchie's study of meningeal SFTs, there was no significant difference between histology and NAB2-STAT6 fusion gene, while there was a significant difference between histology and tumor with/without NAB2 exon 4-STAT6 exon 3 fusion [32].…”
Section: Histology and Variants Of Nab2-stat6 Fusion Genementioning
confidence: 92%
“…The discovery of the NAB2–STAT6 fusion as the driving alteration in SFT suggested that specific chimeric fusion types may drive differential behaviour. But while different exonic fusion types show site and histological phenotype predilections, no correlation between NAB2–STAT6 fusion type and disease‐free survival has been reported to date …”
Section: Introductionmentioning
confidence: 99%